Management of idiopathic chylopericardium in Pregnant Patient. (October 2016) - Rafiq, Muhammad Umar; Ali, Jason; Saad, Haisam; Wilson, Stephen; Van Tornout, Filip
Idiopathic chylopericardium in pregnancy is extremely rare and poses difficulties in both decision-making and timing of surgery. A young lady who was 24-weeks pregnant presented with chylopericardium and increasing shortness of breath. Repeated nonsurgical interventions failed to resolve her pathology. She underwent thoracoscopic pericardial window formation and thoracic duct ligation, and made a satisfactory recovery.